Marka Hukukunda Sessiz Kalma Yoluyla Hak Kaybının Gerçekleşmesi İçin Gereken Sessiz Kalma Süresi - IŞIK, EGEMEN (My University, 2024)
Marka hukukunda sessiz kalma yoluyla hak kaybının gerçekleşmesi için kanun koyucu tarafından belirlenmiş süre boyunca sessiz kalınması gerekmektedir. Bu süreyi, konunun ruhuna uygun olarak “sessiz kalma süresi” olarak adlandırmak mümkündür. Sessiz kalma süresinin uzunluğu tartışmaya yer bırakmayacak şekilde kanunda belirtilmiştir. Bununla birlikte sessiz kalma süresinin hukuki niteliği ile özellikle sürenin başlaması ve sona ermesine ilişkin açıklığa kavuşturulması gereken pek çok nokta vardır. Çalışmamız ile amaçlanan sessiz kalma süresine ilişkin sorunların öğretideki görüşler ve mahkeme kararları esas alınarak tartışılmasıdır. ANAHTAR KELİMELER: Sessiz Kalma, Sessiz Kalma Yoluyla Hak Kaybı, Sessiz Kalma Süresi, Marka Sahibinin Sessiz Kalması, Beş Yıl Boyunca Sessiz Kalma

In order for the loss of right due to remaining silent in Trademark Law, it is necessary to remaining silent for the period determined by the legislator. It is possible to call this period the “period of silence” in accordance with the spirit of the subject. The length of the period of silence is specified in the law without the need for any discussions. However, there are many points that need to be clarified regarding the legal nature of the period of silence and especially the start and end of the period. The aim of this study is to discuss the problems related to the period of silence based on the views in the doctrine and court decisions. KEYWORDS: Remaining Silent, The Loss of Right Due to Remaining Silent, Period of Silence, Silence of the Trademark Holder, Remaining Silent for Five Years
Required silence period for the realization of loss of right due to remaining silent in trademark law
Keywords: Sosyal ve Beşeri Bilimler; Hukuk; Social Sciences and Humanities; Law; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; HUKUK; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; LAW; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Sessiz Kalma; Sessiz Kalma Yoluyla Hak Kaybı; Sessiz Kalma Süresi; Marka Sahibinin Sessiz Kalması; Beş Yıl Boyunca Sessiz Kalma; Remaining Silent; The Loss of Right Due to Remaining Silent; Period of Silence; Silence of the Trademark Holder; Remaining Silent for Five Years